Patients with locally advanced cervical cancer should not undergo routine pretreatment surgical staging - Mota, F (2006)
The current FIGO staging system for locally advanced cervical cancer (Stages IIB to IVA) is considerably inaccurate, especially because lymph node metastases are ignored. Surgical staging has been used to overcome this insufficiency, allowing individualisation of therapy. However, this approach is controversial and should not be routinely undertaken considering the feasibility, adequacy and morbidity involved with the surgical procedure. Moreover, the survival benefit of surgical staging has yet to be proven and accurate non-invasive imaging alternatives, such as position emission tomography (PET) scanning, have become available. The management of patients with locally advanced cervical cancer based on PET and computed tomography (CT) imaging is proposed and discussed.